Analysis of The Influence of Retail Mix on Purchase Decision: A Study on Balikpapan Vega Milenial Building Store - Khadizah, Nurul Ulfa (Universitas Ciputra Surabaya, 2022)
The contribution of the construction sector in Balikpapan City to the city's GRDP every year there is an increase because one city / regency in East Kalimantan is predicted to become the new State Capital. Vega Milenial Balikpapan store is a business store engaged in retailing building materials, power tools, and engineering tools which was established in 2020. The purpose of this research is to analyze the effect of the product on price, promotion, location, people, and physical evidence on purchase decisions in the Vega Milenial Balikpapan building store with variables product (X1), price (X2), promotion (X3), location (X4), people (X5), and physical evidence (X6) on purchase decision (Y). This research is quantitative with the population of customers of Vega Millenial Building Store from July 2021 to March 2022. The sample of this research is 135 samples who have purchased products at the Vega Milenial Building Shop. Data collection method of this research uses questionnaire and the technique of this research is Multiple Linear Regression by being using SPSS software. The result of this research product, price, and promotion does not affect significant on Vega Milenial store purchase decision. Location, people, and physical evidence does affect significantly on Vega Milenial Building Store purchase decision.